2005
DOI: 10.4103/0971-9261.16466
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of postoperative results in anorectal malformations

Abstract: ABSTRACT ABSTRACT ABSTRACTSurgery for the correction of anorectal malformations (ARM) is performed by almost all pediatric surgeons. A number of operative procedures are practiced. The posterior sagittal anorectoplasty procedure has found wide acceptability and although it provides the most accurate anatomical reconstruction of the neoanorectum and the sphincters, the results are not in keeping with this technical advantage. In addition, there is no uniformity in describing the results of surgery and hence com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Size of anal opening, anal tone, and bowel habits were assessed during follow-up visits. The results (postoperative fecal continence) were judged by Kelly's continence score,[ 9 ] 6 months, 1 year, and 4 years postoperatively. The follow-up period ranged from 1 to 4½ years [ Table 1 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Size of anal opening, anal tone, and bowel habits were assessed during follow-up visits. The results (postoperative fecal continence) were judged by Kelly's continence score,[ 9 ] 6 months, 1 year, and 4 years postoperatively. The follow-up period ranged from 1 to 4½ years [ Table 1 ].…”
Section: Methodsmentioning
confidence: 99%
“…Proximal diversion in the form of window colostomy, proximal ileostomy, end colostomy after division of fistula, or end colostomy after coloplasty has been described as the first step. [ 9 11 ] None of the above, best-suited our case. Here, the pouch was grossly dilated and fecally loaded.…”
Section: Methodsmentioning
confidence: 99%
“…The study also found that anorectal manometry assesses functional compliance, correlates well with Kelly's score and can predict long-term results, and should be used for decision regarding re-operation. 17 We had one child who underwent SPM, and the child had persistent urinary leak from the neorectum following SPM. The child was treated with a redo surgery (PSARP).…”
Section: Discussionmentioning
confidence: 99%
“…In the study Urological problems or faecal continence during long-term follow-up of patients with anorectal malformation, Senel E et al reported that urinary system pathology was detected in 35 (37.6%) of the cases with 22 (23.7%) having severe uropathology. 12 As per the study, Assessment of postoperative results in anorectal malformations, V Bhatnagar et al 14 reported that the incidence of postoperative urinary incontinence in ARM patients ranges from 0 to 10% in patients with low ARM, up to 28% in patients with high ARM in the pre-PSARP period and significant reduction in the post-PSARP period (8-10%). Studies have shown that a high percentage of preoperative patients with ARM have occult neurovesical dysfunction (small capacity bladder, uninhibited detrusor contractions, poor compliance, etc.)…”
Section: Armmentioning
confidence: 95%